Metabolomics analysis reveals variation in Schisandra chinensis cetabolites from different origins. Issue 6 (March 2014) - Zhang, Yinan; Li, Fen; Huang, Fengjie; Xie, Guoxiang; Wei, Runmin; Chen, Tianlu; Liu, Jiajian; Zhao, Aihua; Jia, Wei
<x xml:space="preserve">Abstract</x> Wu Wei Zi (Schisandra chinensis), an important herbal medicine, is mainly distributed in the northeast of China. Its phytochemical compositions, which depend on geographical origin, climatic conditions and cultural practices, may vary largely among Wu Wei Zi from different areas. In this study, we applied a comprehensive metabolite profiling approach using GC–TOF‐MS, ultra‐performance LC (UPLC) quadrupole TOF (QTOF) MS and inductively coupled plasma MS to systematically investigate the metabolite variations of S. chinensis from four different areas including Heilongjiang, Liaoning, Jilin, and Shanxi of China. A total of 65 primary metabolites, 35 secondary metabolites and 64 inorganic elements were identified. Several primary metabolites, including shikimic acid and tricarboxylic acid cycle intermediates, were abundant in those located in Heilongjiang, Jilin, and Liaoning. Besides, bioactive lignans are also highly abundant in those from northeastern China than those from northwestern China. Inorganic elements varied significantly among the different locations. Our results suggested that the metabolite profiling approach using GC–TOF‐MS, ultra‐performance LC quadrupole TOF MS, and inductively coupled plasma MS is a robust and reliable method that can be effectively used to explore subtle variations among plants from different geographical locations.